Pharmacokinetics of a novel triazine ethanamizuril in rats and broiler chickens. (April 2018) - Cheng, Peipei; Wang, Chunmei; Lin, Xi; Zhang, Lifang; Fei, Chenzhong; Zhang, Keyu; Zhao, Juan; Lei, Na; Liu, Lili; Mu, Shuhua; Wang, Xiaoyang; Wang, Mi; et al.
Abstract: Ethanamizuril is a new triazine compound that displays potent anticoccidial activity against chicken coccidiosis caused by Eimeria tenella . We studied the pharmacokinetics of ethanamizuril in rats and chickens after single oral doses of one, two and three times the minimum effective dose Ethanamizuril was readily absorbed at all three doses and the plasma concentration reached was maximal within 5 h and progressively declined over time. The mean peak plasma concentrations (Cmax ) and the area under the concentration − time curve (AUC) were both dose-dependent. These results provide pharmacokinetic profiles of ethanamizuril for future preclinical studies and clinical use. Highlights: Ethanamizuril (EZL), a new triazine compound, with excellent anticoccidial activity against chicken coccidiosis caused by Eimeria tenella . Pharmacokinetics of EZL in Rats and broiler chickens were studied. There were dose-dependent increases in mean peak plasma concentrations (Cmax ) and concentration − time curve (AUC) between different dosage groups.